A venture capital model of the development process for new ventures - Ruhnka, John C.; Young, John E. (Journal of Business Venturing, 1987)
For years, researchers have hypothesized that new ventures develop in a fairly predictable chronological process by evolving through various functional and strategic developmental stages. However, cross-comparable longitudinal data from large numbers of ventures are still not available to validate these “stages of development” hypotheses. The study sought to determine whether venture capital firms, which have extensive experience with the longitudinal development of new ventures, operate in accord with a common theory about how this process operates. These findings also represent a first step toward empirically validating various elements of “stages of development” theories. The study analyzed the perceptions of the CEO or managing partner of 73 U.S. venture capital firms about key features of the development process for new businesses. Venture capital firms were asked whether they differentiated stages in the development process. For each such stage information was elicited on what the stage was called, distinguishing characteristics of ventures in that stage, key developmental goals or benchmarks typically accomplished in that stage, and the major risks involved. Sufficient consensus was found on these aspects of the development process for a “venture capital model” of this process to be constructed. The model consists of five sequential stages: 1) “seed” ; 2) “start-up” ; 3) “second stage” ; 4) “third stage” ; and 5) “exit stage.” Strong consensus was found on distinguishing characteristics of ventures in early stages of development, key developmental goals or benchmarks in various stages, and major developmental risks associated with each stage. Consensus on developmental characteristics diminished somewhat in later stages, presumably because of differential rates of development among investees, as well as differing degrees of success in accomplishing earlier objectives. Nevertheless, sufficient differences in functional characteristics remained to clearly distinguish later stage investees from early stage investees, and to enable differentiations in maturity between “third stage” and “exit stage” investees. The venture capital developmental model exhibits both similarities and differences from “stages of development” paradigms. First, the venture capital model is primarily strategic and market-oriented in focus. It gives lesser emphasis to the elements of organizational structure, management style, and management specialization than some “stages of development” theories, although these elements are identified by venture capitalists as potential areas of risk should problems arise. Second, like “stages of development” paradigms, the venture capital model is universal and not venture specific. Venture capital firms appear to view all potentially feasible business concepts, despite differences in product, organizational complexity, rate of development, or ultimate size, as passing through the same process sequence, albeit at different speeds and with varying degrees of success. Third, the model, while reflecting the financial objectives of venture capital investors, is primarily shaped by the naturally occurring functional development of investees. It does not represent arbitrary requirements imposed on investees to segment the developmental process into steps that would not otherwise occur. The development of venture capital investees is influenced by the strategic and financial objectives of venture capital firms. Thus the model does not necessarily mirror the strategic and dynamic elements of the development process for firms that are not intended by their founders to grow rapidly and then go public or be acquired by a larger corporation, or for ventures that must depend upon internally generated funds or bank loans to finance development. The venture capital model, representing perceptions of 73 venture capital firms derived from longitudinal data for many hundreds of new ventures, appears to empirically confirm the concept of an evolutionary progression through key functional and strategic steps, which is a central element of most “stages-of-development” hypotheses. The study did not go into sufficient depth, however, to provide detail on the influence of factors such as organizational structure and management styles and control systems on development. These factors are central elements in several “stages of development” theories, and are arguably of critical importance in the growth, survival, and financial success of new ventures.